(untitled) (Proceedings of International Educators Conference, 2024)
Cytomegalovirus (cytomegalovirus, CMV, SMV) is a virus belonging to the herpes family that affects internal organs and the central nervous system and is practically asymptomatic. People become infected with this virus mainly when their immunity is weakened (for example, due to AIDS). When the virus affects internal organs, weakness, diarrhea, and constipation are observed. With injuries to the genitourinary organs, the disease manifests itself as inflammation of the uterus (endometritis), inflammation of the cervix (cervicitis), inflammation of the vagina (vaginitis) in women, and in men it is predominantly asymptomatic (without symptoms). The disease can also take the form of ARVI (acute respiratory diseases). Cytomegalovirus infection in pregnant women can lead to the development of pathologies of pregnancy, fetus or child.